Steno-Entrepreneurship Skill Retrainings: A Veritable Tool as Emerging Reality in Quality Business Education for Developing Nation - Ozuruoke, A. A; Onwuchekwa, C.A; Ogolo, F. I; Eniang, O.U (Richtmann Publishing, 2011)
This paper opines that entrepreneurship Skill be combined with Stenographic Skill to have a common name STENOENTREPRENEURfor quality education that inculcate two viable skills into one for Business Educators and be offered at regularworkshops at given intervals. This can keep the undertaker at a more advantageous position for effective role performance in adeveloping nation where unemployment is a societal problem as in Nigeria today. It agitates here as presented in a twelve slidespower point. It explains what is meant by steno- entrepreneurship and spelt out the qualities and functions expected of suchpersonnel. Motivating factors and strategies for inculcating such desired skill were fully presented. This paper further agitatesthat multinational companies, banks and financial houses which records have shown their high profit margin over others bemade to aid a developing nation like Nigeria to finance such steno- entrepreneurship skill acquisition programme. The paper alsoaffirmed that such resources can be tapped to enhance the teaching and learning quality education programmes in stenoentrepreneurshipskill as solution to challenges for effective and efficient education and for developing nations.